Europec/Eage Conference and Exhibition 2008
DOI: 10.2118/112794-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Acidizing of a HTHP Exploratory Well in Deep Carbonate Reservoir: A Case Study

Abstract: The Jurassic carbonate reservoirs in Kuwait are deep, characterized with extremely low porosity and permeability. The temperature of these reservoirs ranges between 250–300ºF. High production from these types of reservoirs will be possible if the oil filled fractures can discharge into large connected fractures during drawdown. Hence, these reservoirs are well sited for fracture stimulation to be exploited properly. Fracture acidization of a deep HTHP exploratory well producing from limestone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Al‐momin et al studied the effects of contact time, type of acid system, and treatment temperature on the electrical conductivity of the San Andres dolomite core 21 . Al‐Omair et al discussed the procedural mechanisms for the selection of stimulation techniques (acidification or proppant) in deep limestone reservoirs 22 . Beg et al studied the relationship between the acid contact time and the conductivity of fractures, and the results showed that increasing the acid contact time sometimes led to a decrease in the conductivity of fractures, and sometimes increased the conductivity of fractures 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al‐momin et al studied the effects of contact time, type of acid system, and treatment temperature on the electrical conductivity of the San Andres dolomite core 21 . Al‐Omair et al discussed the procedural mechanisms for the selection of stimulation techniques (acidification or proppant) in deep limestone reservoirs 22 . Beg et al studied the relationship between the acid contact time and the conductivity of fractures, and the results showed that increasing the acid contact time sometimes led to a decrease in the conductivity of fractures, and sometimes increased the conductivity of fractures 23 …”
Section: Introductionmentioning
confidence: 99%
“…21 Al-Omair et al discussed the procedural mechanisms for the selection of stimulation techniques (acidification or proppant) in deep limestone reservoirs. 22 Beg et al studied the relationship between the acid contact time and the conductivity of fractures, and the results showed that increasing the acid contact time sometimes led to a decrease in the conductivity of fractures, and sometimes increased the conductivity of fractures. 23 At present, research on the conductivity of acid corrosion fractures mainly focuses on acid fracturing design methods, testing the conductivity of different types of acid fluids, and analyzing the influencing factors of fracture conductivity.…”
Section: Introductionmentioning
confidence: 99%